Pengaruh Resistansi Koil dan Konduktivitas Termal Busi terhadap Daya Sepeda Motor Injeksi 150 cm3 - Brilyan Ramadhani; Santoso Santoso (Journal of Creative Student Research, 2024)
Spark plugs and ignition coils are important components in creating sparks in the combustion chamber. Sparks can be weakened by spark plug electrodes that are worn out due to time of use. Worn electrodes will cause the gap to increase, thus requiring a higher secondary voltage. This study aims to determine the effect of ignition coil resistance and spark plug thermal conductivity on 150 cm3 injection motorcycle power. The method used is an experimental method with a quantitative approach. The independent variables used in this study are ignition coil resistance with values of 3.0 Ω, 3.4 Ω, 3.8 Ω and spark plug thermal conductivity of nickel 90.9 W/m.K, platinum 71.6 W/m.K, and iridium 147 W/m.K. The results showed that the highest power was obtained at engine speed of 8500 rpm using ignition coil resistance of 3.0 Ω with spark plug thermal conductivity of iridium 14.10 hp, nickel 13.75 hp, and platinum 13.61 hp. The lowest power was obtained at engine speed of 5500 rpm using an ignition coil resistance of 3.8 Ω with a spark plug thermal conductivity of iridium 13.72 hp, nickel 13.67 hp, and platinum 13.59 hp.